Program Evaluation Work Group Teacher Physical Education Sports and Health Primary Schools in Alian District Kebumen Regency (Journal of Physical Education and Sports, 2019)
Teacher Working Groups (KKG) are very strategic to improve teacher competency and performance. Various efforts to improve teacher performance, including through various instructor training, attending seminars and training, and improving the quality of KKG management. Improvement and development of teacher professional abilities include various aspects including the ability of teachers to master the curriculum and teaching materia, the ability to use methods and facilities in the teaching and learning process, carry out assessment of the process and learning outcomes and the ability to use the environment as a source of learning, discipline and have a commitment to the task. The role of the KKG is very important in developing the teaching profession, through the routine activities of the Penjasorkes teacher KKG in Alian District, it can strengthen brotherhood between teachers, increase insight, improve teacher competence, be able to administer learning together, increase motivation to learn to a higher level of education. . In addition, various problems faced by teachers in the learning process can be resolved through discussions between teachers.. Evaluation of the Countence model of Stake includes 3 things namely antecedents, transactions and outcomes. The results of the antecedent evaluation research (input) show that the PJOK KKG program in Alian Subdistrict, Kebumen Regency has been well organized and planned according to the AD / ART that has been made, a clear vision and mission and goals. Transaction evaluation (process) shows that the implementation of PJOK KKG activities in Alian Subdistrict, Kebumen Regency has not run according to the program that has been made. For the evaluation of outcomes, the results achieved by PJOK teachers from the PJOK KKG activities in Alian District, Kebumen Regency have not been maximized.